Positive correlation between symptoms and circulating motilin, pancreatic polypeptide and gastrin concentrations in functional bowel disorders. Issue 10 (October 1985) - Preston, D M; Adrian, T E; Christofides, N D; Lennard-Jones, J E; Bloom, S R
Abstract : Motilin, pancreatic polypeptide and gastrin blood concentrations in response to drinking water have been studied in 40 patients with functional bowel disease and compared with results in two groups of healthy control subjects. Patients with slow transit constipation and idiopathic megacolon showed impaired motilin release. Pancreatic polypeptide release was reduced in patients with slow transit constipation, but increased in those with functional diarrhoea. Gastrin release was impaired in all groups complaining of chronic constipation. Circulating motilin, pancreatic polypeptide and gastrin concentrations appear to bear some relationship to intestinal transit time in patients with functional bowel disorders.